Synthesis, Characterization, Cytotoxicity Analysis and Evaluation of Novel Heterocyclic Derivatives of Benzamidine against Periodontal Disease Triggering Bacteria - Ramasamy Kavitha; Mohammad Auwal Sa'ad; Shivkanya Fuloria; Neeraj Kumar Fuloria; Manickam Ravichandran; Pattabhiraman Lalitha (MDPI AG, 2023)
Periodontal disease (PD) is multifactorial oral disease that damages tooth-supporting tissue. PD treatment includes proper oral hygiene, deep cleaning, antibiotics therapy, and surgery. Despite the availability of basic treatments, some of these are rendered undesirable in PD treatment due to side effects and expense. Therefore, the aim of the present study is to develop novel molecules to combat the PD triggering pathogens. The study involved the synthesis of 4-((5-(substituted-phenyl)-1,3,4-oxadiazol-2-yl)methoxy)benzamidine (5a-e), by condensation of 2-(4-carbamimidoylphenoxy)acetohydrazide (3) with different aromatic acids; and synthesis of 4-((4-(substituted benzylideneamino)-4H-1,2,4-triazol-3-yl)methoxy)benzamidine (6a-b) by treatment of compound 3 with CS2 followed by hydrazination and a Schiff reaction with different aromatic aldehydes. Synthesized compounds were characterized based on the NMR, FTIR, and mass spectrometric data. To assess the effectiveness of the newly synthesized compound in PD, new compounds were subjected to antimicrobial evaluation against P. gingivalis and E. coli using the micro-broth dilution method. Synthesized compounds were also subjected to cytotoxicity evaluation against HEK-293 cells using an MTT assay. The present study revealed the successful synthesis of heterocyclic derivatives of benzamidine with significant inhibitory potential against P. gingivalis and E. coli. Synthesized compounds exhibited minimal to the absence of cytotoxicity. Significant antimicrobial potential and least/no cytotoxicity of new heterocyclic analogs of benzamidine against PD-triggering bacteria supports their potential application in PD treatment.